Volume Gap Theorems for Ricci Nonnegative Metrics and Einstein Metrics (Journal of Mathematical Study, 2025)
In this note, we prove some gap theorems of asymptotic volume ratio forRicci nonnegative metrics, and gap theorems of volume for Einstein metrics.